THE AUTHORITY OF INVESTIGATORS TO TERMINATE INVESTIGATIONS FROM A LEGAL PERSPECTIVE IN INDONESIA - Prasetyoandi, Destri (Journal Philosophy of Law, 2024)
This study aims to understand how law enforcement is regulated according to Law Number 8 of 1981 and how the criminal investigation process can be terminated by investigators. This research uses normative legal research methods, utilizing both primary and secondary data. The research approach used is a legislative approach. The results of the study show that in the Indonesian Code of Criminal Procedure (KUHAP), there are provisions that allow law enforcement officers, especially investigators and public prosecutors, to discontinue a criminal case from proceeding to trial. This can be done through the termination of investigation or prosecution. However, the authorities stipulated in the KUHAP to discontinue a criminal case to court, such as the termination of investigation and prosecution, do not provide a legal basis for investigators to settle cases peacefully. Instead, the KUHAP follows the principle of legality in prosecution, obliging investigators and public prosecutors to prosecute all cases that meet legal requirements in court, in accordance with Article 140 paragraph (2) linked to Article 14 of the KUHAP. Although Article 140 paragraph (2) of the KUHAP indicates that the KUHAP does not adopt the principle of opportunity in prosecution but follows the principle of legality, the explanation of Article 77 of the KUHAP acknowledges the principle of opportunity. This principle gives authority to public prosecutors to postpone or suspend a case that actually meets the legal requirements for prosecution, for the public interest. However, this authority cannot be a legal basis for settling cases peacefully outside of court, as reasons of interest in peaceful settlement cannot be considered as reasons of public interest, as explained in the Explanation of Article 35 Letter c of the Indonesian Prosecutor Law No. 16 of 2004.